PENGARUH METODE DISKUSI, METODE RESITASI, DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR IPS - munaji munaji (INSPIRASI : JURNAL ILMU-ILMU SOSIAL, 2017)
The purpose of this study are: To Knowing there is influence between the use of discussion and recitation method and learning motivation to IPS learning outcomes in grade VIII SMPN 1 Tanggunggunung Tulungagung. From the data analysis can be concluded as follows: (1) There is a significant influence of learning with the method of discussion on the results of IPS learning in grade VIII students SMPN 1 Tanggunggunung Tulungagung regency, as evidenced from the analysis of discussion method variable (X1) obtained t count ttable, that is 2.104 2,000 and significant 0.040 0.05. (2) There is a significant effect of learning with recitation method of IPS learning outcomes in grade VIII students SMPN 1 Tanggunggunung Tulungagung regency, proved the result of recitation method method with learning result obtained t value t table (11,045 2,000) and significant 0,000 0 , 05. (3) There is a significant influence of learning motivation on IPS learning outcomes in grade VIII students SMPN 1 Tanggunggunung Tulungagung regency, as evidenced from the analysis of t count t table (2,475 2,000) and significant 0.017 0.05. (4) There is influence simultaneously or simultaneously the use of discussion method, recitation method and learning motivation toward IPS learning result in grade VIII student SMPN 1 Tanggunggunung Tulungagung regency, proved F count F table (74,575 2,730) and significant 0,000 0.05